Visible light-mediated intramolecular C–H arylation of diazonium salts of N-(2-aminoaryl)benzoimines: a facile synthesis of 6-arylphenanthridines. Issue 10 (5th August 2016) - Natarajan, Palani; Kumar, Naveen; Sharma, Manjeet
Abstract : 6-Arylphenanthridines were synthesized in good to excellent yields from inexpensive and environmentally benign N -(2-aminoaryl)-diphenylmethanimine as a starting material under visible light-photocatalyzed conditions. Abstract : Utilizing [Ru(bpy)3 ]Cl2 as a photoredox catalyst and a blue LED as an irradiation source, moderate to good yields of 6-arylphenanthridines were obtained from aryl diazonium salts in situ formed from the reactions of N -(2-aminoaryl)benzoimines and tert -butyl nitrite ( t BuONO). Although few visible light-mediated protocols are available for the synthesis of 6-arylphenanthridines, this work provides a new method to access them readily from inexpensive and environmentally benign starting materials.